2018
DOI: 10.1111/jopy.12433
|View full text |Cite
|
Sign up to set email alerts
|

The role of change in self‐criticism across young adulthood in explaining developmental outcomes and psychological wellbeing

Abstract: Objective Past research has confirmed the role of self‐criticism in numerous forms of psychopathology and negative interpersonal outcomes. However, the majority of these studies were cross‐sectional and have not addressed the role of possible changes in self‐criticism across time for future outcomes. The current study investigated the degree to which changes in self‐criticism during young adulthood precede better psychological outcomes beyond the contribution of their baseline levels. Method A total of 168 Isr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…Relatedly, there is also some earlier evidence that a decrease in self-criticism over time associates with better future adaptation. Decrease in self-criticism explained a decrease in level of depression (Kopala-Sibley et al, 2016) and associated with greater future achievement of developmental tasks such as career development, and better psychological well-being (Michaeli et al, 2019). The current study is unique in that it examined the role of self-criticism and its change over time in a particular life context-the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Relatedly, there is also some earlier evidence that a decrease in self-criticism over time associates with better future adaptation. Decrease in self-criticism explained a decrease in level of depression (Kopala-Sibley et al, 2016) and associated with greater future achievement of developmental tasks such as career development, and better psychological well-being (Michaeli et al, 2019). The current study is unique in that it examined the role of self-criticism and its change over time in a particular life context-the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…The current study is unique in that it examined the role of self-criticism and its change over time in a particular life context-the Covid-19 pandemic. Considered together, it can be suggested that personality attributes affect not only concurrent coping with daily aggravations, or negative life events (e.g., Besser & Priel, 2010;Blatt, 2004;Sherry et al, 2014) or coping with developmental tasks (Michaeli et al, 2019), they play a role in the mode in which a person will address an unexpected challenge such as the Covid-19 pandemic. Contrary to our expectation, efficacy signifying dispositional competence and confidence in oneself was not associated with any Covid-19-related psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fields of clinical medicine, early childhood education, and psychology there is a need for some psychological assessment of young children, with the aim of correctly understanding the current psychological-behavioral state [1][2][3]. On the one hand, it is necessary to determine the child's psychological development, and on the other hand, it is necessary to identify the presence of behavioral problems and psychological developmental disorders so that early education, early intervention, and early treatment can be targeted [4][5]. There are many types of psychological assessments for young children, which are divided into cognitive, such as perceptual, language tests, emotional-behavioral assessments, aptitude tests, and personality tests according to the psychological domains involved [6][7][8].…”
Section: Background Of the Studymentioning
confidence: 99%